(untitled) (World Bulletin of Social Sciences, 2026)
The issues of developing students’ reading literacy and essay writing skills in Uzbek language education are discussed. The author substantiates the interdependence of listening comprehension, reading, speaking and writing skills in language teaching. The article scientifically and methodologically analyzes effective methods of organizing listening activities, criteria for selecting educational materials, and principles for developing tasks